FORMATION OF ESTIMATED CONDITIONS FOR LIFE CYCLE OF DEFORMATION WORK OF THE RAILWAY TRACK - Bondarenko, I. O. (Science and Transport Progress, 2015)
Purpose.The purpose of this research is to substantiate the technical limits of the railway track (under reliability status) for the formation the regulatory framework for reliability and functional safety of the railway track in Ukraine. Methodology.In order to achieve the goal of research analysis methods of the technical states of elements and trackforms that are typical of operation conditions of the railways in Ukraine were used. Findings.Technical states accordance of elements and trackforms to reliability status under existing regulations was defined. These conditions are based on the track assessments in accordance with the dimensional tape results. The status of each element of the track design affects its deformation work, but the rules are still absent that would connect state of track elements with the state of the track by estimation of the dimensional tape. The reasons on which the limits are not set were established. It was found out which researches are necessary to conduct for their installation. Originality. The classification of the reliability state of a railway track for permitted deviation at the track laying and maintenance was developed. The regulation importance the technical states of ballast section and subgrade for the developed classification was established. Practical value. Ukrzaliznytsia (UZ) is a founding member of the Council for Railway Transport of the Commonwealth. This body issued interstate standard State Standard 32192-2013 «Reliability of railway equipment. Basic concepts, terms and definitions». On this basis developed a new interstate standard «Security functional of railway equipment. Terms and definitions». At the same time UZ is a member of the cooperation of railways in International Union of Railway Transport where rules with reliable and safe operation of railways are established in all transport branches. This study will help implement these standards on the railways of Ukraine, improve the efficiency of the information in this sphere, providing mutual understanding and unity of presentation and perception of information, including contractual legal relations of economic agents with public authorities in international scientific and technical, trade and economic relations.